2014
DOI: 10.1007/s11255-014-0810-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions and psychological disorders associated with type IIIa chronic prostatitis: a clinical survey in China

Abstract: Our data indicate that a moderate level of sexual dysfunctions exists among the type IIIa CP patients, and highlight the association of depression and anxiety with erectile dysfunction in CP patients, suggestting that special attention should be paid to these psychological issues in clinical treatments of the prostatitis symptoms and the associated erectile dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…Psychological factors may also be the link to a relationship between prostatitis and sexual function [ 26 ]. Furthermore, psychological comorbidities are common in males with prostatitis, and it may be a factor involved in the mechanism of impaired erectile function [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological factors may also be the link to a relationship between prostatitis and sexual function [ 26 ]. Furthermore, psychological comorbidities are common in males with prostatitis, and it may be a factor involved in the mechanism of impaired erectile function [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, psychological comorbidities are common in males with prostatitis, and it may be a factor involved in the mechanism of impaired erectile function [ 27 ]. In psychological aspects, the most common of these risk factors are anxiety or depression, which can have an adverse effect on sexual function [ 26 , 28 ]. Patients with prostatitis have a high incidence of sexual dysfunction due to psychological reasons, and patients with prostatitis have more severe stress, depression, anxiety, and adverse impairment of sexual function [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars believe that >80% of category III CP/CPPS patients have certain psychological problems, of which 20-50% might be serious. 16 Mental disorders in category III CP/CPPS patients was mainly manifested as depression, anxiety, energy loss and other symptoms. 17 Henkel found that anxiety and depression are more prevalent in category III CP/CPPS patients, and interferes the patient's complete recovery, affecting the patient's quality of life and work efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This dysuria is either the consequence of a stenosis of the urethra which is complicated by chronic prostatitis, or due to a defect of opening of the vesical neck sheathed by chronic prostatitis. For some authors, premature ejaculation in patients with chronic prostatitis would be due to prostatic inflammation that would alter the sensation and modulation of the ejaculatory reflex [11] [12] [13]. Fu W et al, [14] even establish a significant link between hypofertility and chronic prostatitis.…”
Section: Discussionmentioning
confidence: 99%